2022
DOI: 10.1097/cin.0000000000000958
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Comparative Pilot Study: Association Between Use of a Self-monitoring Device and Sleep and Stress Outcomes in Pregnancy

Abstract: Pregnancy is a challenging time for maintaining quality sleep and managing stress. Digital self-monitoring technologies are popular because of assumed increased patient engagement leading to an impact on health outcomes. However, the actual association between wear time of such devices and improved sleep/stress outcomes remains untested. Here, a descriptive comparative pilot study of 20 pregnant women was conducted to examine associations between wear time (behavioral engagement) of self-monitoring devices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In total, 20 pregnant women monitored themselves in either a high (n=14, 70%) or a low (n=6, 30%) amount ( Table 2 ) based on the kernel density estimate conducted in our previous study [ 18 ]. Women described that the eHealth system’s mediating activities and their own adaptive activities of self-monitoring enacted a process of cocreation for eHealth system use.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 20 pregnant women monitored themselves in either a high (n=14, 70%) or a low (n=6, 30%) amount ( Table 2 ) based on the kernel density estimate conducted in our previous study [ 18 ]. Women described that the eHealth system’s mediating activities and their own adaptive activities of self-monitoring enacted a process of cocreation for eHealth system use.…”
Section: Resultsmentioning
confidence: 99%
“…What is lacking in many studies on evaluating perinatal self-monitoring systems is a clear definition and examination of patient engagement and associated health outcomes [ 24 ]. A descriptive comparative analysis conducted as part of our larger feasibility study revealed the limitations of only examining the physical use of self-monitoring technology [ 18 ]. The process characteristics will be missed if we do not look beyond physical use as an indicator of engagement [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations